Karakteristik Pasien Demam Tifoid pada Anak dan Remaja - Festy Ladyani Mustofa; Rakhmi Rafie; Ghina Salsabilla (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Typhoid fever is an acute bowel disease caused by the bacterial salmonella typhi or Salmonella paratyphi A, B and C. characteristics of the sufferer of typhoid fever in children and adolescents often founded various kinds are age, gender, duration with a fever, degree of fever, results of the most numerous Widal test, Giving antibiotic drug. And the characteristics will be explained in this research. Aim: To know the characteristics of the patients with typhoid fever in children aged (4-11) years and Adolescents age (12-25) years in the hospital Pertamina Bintang Amin in 2018. Methods: This research is a descriptive study with a qualitative approach. The Sources of user research data were used secondary data obtained based on the medical record data of patients who diagnosed with typhoid fever in children and adolescents at Pertamina Bintang Amin Hospital. The population was 1539. A sample of 317 patients diagnosed of typhoid fever. Data collection in January 2020, data analysis process of univariate analysis. Results: Characteristics of the sufferers of typhoid fever in children and adolescents at Pertamina Bintang Amin Bandar Lampung Hospital in 2018 with the most age were 5-11 years (57.1%). Most genders were women (57.7%). The most degree of fever is febrile fever (93.4%). The most fever duration with a fever of ≤ 1 week (77.0%). The results of the most numerous Widal test were patients with positive results (84.2%). The most history of another test was yes they did (100%). Giving antibiotic drugs was giving antibiotic drugs Line 2 (99.1%). Conclusion: Based on these results, characteristics of the sufferer of typhoid fever in children and adolescents at Pertamina Bintang Amin Hospital in 2018 which is aged 5-11 years, with female gender, degree of febrile fever, old fever of ≤ 1 week, test results Positive, the history of conducting other checks is yes, giving antibiotics drugs is antibiotic drugs line 2 which is ceftriaxone and cefixime